A New Computational Method Based on Integral Transform for Solving Linear and Nonlinear Fractional Systems - Diyar Hashim Malo; Rogash Younis Masiha; Muhammad Amin Sadiq Murad; Sadeq Taha Abdulazeez (Jurnal Matematika MANTIK, 2021)
In this article, the Elzaki homotopy perturbation method is applied to solve fractional stiff systems. The Elzaki homotopy perturbation method (EHPM) is a combination of a modified Laplace integral transform called the Elzaki transform and the homotopy perturbation method. The proposed method is applied for some examples of linear and nonlinear fractional stiff systems. The results obtained by the current method were compared with the results obtained by the kernel Hilbert space KHSM method. The obtained result reveals that the Elzaki homotopy perturbation method is an effective and accurate technique to solve the systems of differential equations of fractional order.